ISOTOPIC COMPOSITION OF THE SULFUR IN PYRITE AND PYRRHOTITE SYNTHESIZED AT 300 TO 500°C AND 1 KBAR - Likhoydov G.G.; Suvorova V.A. (My University, 1989)
The isotopic composition of the sulfur in synthetic pyrite (Pt) and pyrrhotite (Pr) was studied as a function of the reaction temperature (T) and oxygen fugacity fO2. These minerals were synthesized by the hydrothermal process in ampoules placed in an autoclave. The pressure Ptot was 1 kbar, and the temperatures were 300°, 400° and 500°C. The pressure was controlled by the degree of filling of the autoclave. The temperature was measured with an error of ±10°C. Preliminary experiments on kinetics of the reaction proved that the reactions go to completion in 30 to 40 hours. No changes were discernible by our analytical method after that time.